FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP SET KESEMPATAN INVESTASI (IOS) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Reni Yendrawati; Feby Rezki Adhianza (Asian Journal of Innovation and Entrepreneurship, 2013)
The increase inhigh-growth companies and rapidly be characterized by highlevels of investment opportunity set. IOS provides guidance where the value ofthe company as the company's goals dependson investment opportunities and spending in the future. This Study aims to identify and examine the dividend policy, the investment risk, profitability, liquidity, activity and solvency of the investment opportunity set. The population in this study all manufacturing companies listed on the Indonesian Stock Exchange from 2008 to 2011. While sampling technique using purposive sampling that sample with certain criteria, such as having complete financial statement data, has positive earnings and pay dividends in a row from 2008 to 2011. The number of samples that meet the criteria of a sample of 33 companies. To test the hypothesis proposed using multiple linear regression analysis. The test results found that dividend policy has a negative impavt on the invesment opportunity set, profitability and activity positively to the opportunity to grow the company. While the risk of investment, liquidity and solvency ratio did not affect the growth opportunities of the company.Keywords : Dividend Policy, Investment Risk, Profitability, Invesment Opportunity Set